The palette of a 16th century Venetian artist: materials and methods of Giovanni da Mel - Impallaria, Anna; Tisato, Flavia; Petrucci, Ferruccio; Dal Colle, Maurizio; Ruggio, Emanuela (Ge-conservacion, 2017)
Giovanni da Mel (1480-1549) was an Italian Renaissance artist. He worked in the Veneto region and devoted himself to the fresco technique, in his family workshop. During the last part of his life, in the church of Trichiana (Belluno), he painted an altarpiece, which seems to be his only work on canvas. Thanks to the collaboration between restorers and scientists, it was possible to explore in depth this peculiar painting. The imaging techniques helped in the identification of the artistic methodology, for example highlighting the use of engraving the preparation to draw (typical of the fresco technique). Then, the application of spot analysis allowed the identification of the artist’s palette, revealing some peculiarities as the addition of a copper based pigment to the bone black, in order to dry the oil. The diagnostic techniques have fully characterized the altarpiece from a methodological and material point of view.